Analisis Kinerja Keuangan Pada Pt Berkah Wakaf Indonesia (Wahdah Water) - Wahyudin Wahyudin; Romansyah Sahabuddin; Nurman; Anwar; Annisa Paramaswary Aslam (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose this research is determine the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) using financial ratio analysis, specifically liquidity, solvency, activity, profitability, and roe. This study employs a descriptive quantitative research method. The findings indicate that the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) year 2021-2023, viewed from the liquidity ratio measured current ratio, is in poor condition. Furthermore, the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) year 2021-2023 viewed from the solvency ratio measured debt to assets ratio, in poor condition. In contrast, the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) year 2021-2023, viewed from the activity ratio measured total asset turnover, in good condition. Additionally, the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) year 2021-2023, viewed from the profitability ratio measured net profit margin, in poor condition. Lastly, the overall financial performance of PT. Berkah Wakaf Indonesia (wahdah water) year 2021-2023, as viewed the return on equity, in poor condition. The significance of this research's findings lies in providing valuable information regarding the financial performance of PT. Berkah Wakaf Indonesia (wahdah water) for the company and other stakeholders interested in obtaining insights into its financial status.